INOVATIONS FOR AN INTEGRATED PUBLIC SERVICE OF 6IN1 ON MARRIAGE CERTIFICATE IN POPULATION AND CIVIL REGISTRATION AGENCY OF SEMARANG REGENCY - Arsih,, Reni; Maesaroh, Maesaroh (Journal of Public Policy and Management Review, 2019)
Public service, one of duties and responsibilities of a government, establishes to advance rights of peoples to get the best quality service in their society. To obtain the quality service, it needs more actions to create innovations as applied by Population and Civil Registration Agency of Semarang Regency, which makes an integrated public service of 6in1 on marriage certificate. This study aims to analyze an integrated public service of 6in1 on marriage certificate attributes and to identify the factors supporting the innovation. The writer uses qualitative descriptive research method to process the data and Rogers' diffusion of innovation theory, which has five attributes of innovations including relative advantage, compatibility, complexity, trial ability and, observability. The result indicates that an integrated public service of 6in1 on marriage certificate has fulfilled four of five innovations attributes, which are relative advantage; compatibility; trial ability and; observability, missed for complexity. These innovations have supporting factors that are organizational, culture, human, organized pressure to obtain the quality. Related to human resources, the writer suggests to decrease the main duties of employees so that it can avoid employees, who have double jobs. Besides, they should have an ability to distribute the jobs, so they can produce the best responsibilities, especially in managing marriage certificate.